Rancang Bangun E-Learning Pronunciation Bahasa Inggris STKIP Setiabudhi Rangkasbitung Berbasis Web - Karyaningsih, Dentik; Siswanto, Puji (ISB Atma Luhur, 2020)
Lecture courses in the English Language Education Study Program of STKIP Setiabudhi Rangkasbitung are still conducted in face-to-face class, so the students who do not attend lectures cannot know the pronunciation material at that time, because the Pronunciation course is a practical course in the English pronunciation system. The E-Learning Pronunciation is built so that lectures can be carried out anywhere and anytime without reducing the quality of the teaching and learning process. Therefore, the students who are left behind can continue to follow the Pronunciation course material, as well as habituating students in utilizing communication and information technology. E-Learning Pronunciation is important to be built to improve the ability of students’ pronunciation when doing distance learning, so that students are clearer and more firm in understanding Pronunciation so that there are no errors in English pronunciation. Participants in this study were first semester students of English education study programs. This study uses an experimental research design with the Prototype System development method and system of testing uses Black box testing.